1978
DOI: 10.1210/jcem-46-4-689
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LRH on Gonadotropin Secretion in Newborn Male Infants

Abstract: The concentrations of LH and FSH were measured in eight male newborn babies, aged 4-6 h, before and after the administration of 25 micrograms synthetic LHR. A comparison was performed with six control newborns receiving normal saline. Both LH and FSH rose significantly in all subjects after LHR administration. Their values were significantly higher than those observed during the control study. These data demonstrate sensitivity of the pituitary gonadotropes to synthetic LHR and a pubertal-type response to LH i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
3
4
0
Order By: Relevance
“…Some boys with mild LH defi- T I M E minutes TIME m~n u t e s ciency may, however, have been included since this is frequently associated with incomplete testicular descent (6). The concentrations of FSH in the present study were in agreement with earlier reports whereas the LH levels were higher, presumably due to methodological differences (1,14,15). The response pattern of the gonadotropins to GnRH was similar to that described in earlier studies ( 1, 14).…”
Section: Discussionsupporting
confidence: 91%
“…Some boys with mild LH defi- T I M E minutes TIME m~n u t e s ciency may, however, have been included since this is frequently associated with incomplete testicular descent (6). The concentrations of FSH in the present study were in agreement with earlier reports whereas the LH levels were higher, presumably due to methodological differences (1,14,15). The response pattern of the gonadotropins to GnRH was similar to that described in earlier studies ( 1, 14).…”
Section: Discussionsupporting
confidence: 91%
“…The brisk rise of B-LH in males from the nadir on day 4 probably represents active endogenous B-LH secretion and thus suggests activity of the hypothalamic-hypophyseal axis. This concept is further supported by the fact that newborn males have responded to exogenous LHRH with a pubertal pattern of LH secretion (16).…”
Section: Lh-hcg (B-lh)mentioning
confidence: 91%
“…The results confirmed previous studies of Meijs-Roelofs and Kramer [1979] that a feedback interaction between the ovary and the hypothalamo-adenohypophysial system may be established during the early days of life in the rat. It has reported that so-called castration cells occur due to the elevated secretion of hypothalamic LHRH triggered by gonadectomy [Arimura et al, 1976], Delitala et al [1978] reported that LH and FSH rose significantly in male newborn babies after LHRH administration. This indicates that the receptor responses to LHRH in the anterior pituitary gland are functional at birth.…”
Section: Arai and Masudamentioning
confidence: 99%
“…Nakai et al [1972] reported that bilateral castration of male rat fetuses on the 21st day of gestation increased the number of PASpositive cells. It is evident that castration cells were induced by an elevation in hypothalamic LHRH after gonadectomy [Arimura et al, 1976], Delitala et al [1978] reported that gonadotrophins significantly rose in human newborn babies (aged 4-6 h) after synthetic LHRH administration. This demonstrates that the sensitivity of the pituitary to LHRH and a pubertal type LH response was already established during the early hours of life in the newborn infant.…”
Section: Introductionmentioning
confidence: 99%